2010
DOI: 10.1093/cvr/cvq270
|View full text |Cite
|
Sign up to set email alerts
|

Foetal nicotine exposure causes PKCε gene repression by promoter methylation in rat hearts

Abstract: this study demonstrates that prolonged nicotine exposure increases the sympathetic neurotransmitter release in the foetal heart and causes programming of PKCε gene repression through promoter methylation, linking maternal smoking to pathophysiological consequences in the offspring heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 45 publications
8
101
0
Order By: Relevance
“…Our recent studies demonstrated that fetal hypoxia increased CpG methylation of the Sp1 binding sites at rat PKCε gene promoter, which contributed to PKCε gene repression in the developing heart (29). Subsequently, our studies also demonstrated a key role of the early growth response factor-1 (Egr-1) binding site in the regulation of PKCε promoter activity in fetal rat hearts (18). Yet, it remains elusive whether heightened methylation of the Egr-1 binding site contributes to sex dimorphism of hypoxia-induced programming of PKCε gene repression in the developing heart.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Our recent studies demonstrated that fetal hypoxia increased CpG methylation of the Sp1 binding sites at rat PKCε gene promoter, which contributed to PKCε gene repression in the developing heart (29). Subsequently, our studies also demonstrated a key role of the early growth response factor-1 (Egr-1) binding site in the regulation of PKCε promoter activity in fetal rat hearts (18). Yet, it remains elusive whether heightened methylation of the Egr-1 binding site contributes to sex dimorphism of hypoxia-induced programming of PKCε gene repression in the developing heart.…”
mentioning
confidence: 59%
“…RNA was extracted from hearts using TRIzol protocol (Invitrogen, Carlsbad, CA). PKCε mRNA abundance was determined by real-time RT-PCR using Icycler Thermal cycler (BioRad) with the primers of 5=-GCGAAGCCCCTAAGACAAT-3= (forward) and 5=-CACCCCAGATGAAATCCCTAC-3= (reverse) (18). Real-time RT-PCR was performed in a final volume of 25 l. Each PCR reaction mixture consisted of 600 nM of primers, 33 units of M-MLV reverse transcriptase (Promega, Madison, WI), and iQ SYBR Green Supermix (Bio-Rad) containing 0.625 unit Taq polymerase; 400 M each of dATP, dCTP, dGTP, and dTTP; 100 mM KCl; 16.6 mM ammonium sulfate; 40 mM Tris·HCl; 6 mM MgSO 4; SYBR Green I; 20 nM fluorescine; and stabilizers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that nicotine downregulates miR-133 and miR-590 by the nicotinic acetylcholine receptor, α7-nAChR, subsequently activates the transforming growth factor (TGF)-β1 receptor and increases the synthesis of TGF-β1 protein, resulting in structural alterations of increased collagen and reduced elastin content in vascular media (34). Additionally, maternal nicotine administration caused programming of protein kinase Cε gene repression through promoter methylation, simultaneously activating the sympathetic nervous system in the fetal heart, which compromised cardiovascular homeostasis (35).…”
Section: Discussionmentioning
confidence: 99%
“…These changes to DNA methylation may have functional consequences, with one of these studies identifying changes in gene expression associated with these methylation changes . There is also some evidence from a rat model for the capacity 88 DNA METHYLATION CHANGES FOLLOWING NICOTINE EXPOSURE for prenatal nicotine exposure (from gestational day 4) to impact on both DNA methylation and expression of protein kinase C epsilon (PKCε) -a gene which encodes for a protein associated with cardiac injury in the fetal heart (Lawrence et al, 2010;Murriel and Mochly-Rosen, 2003). Whether an in utero exposure to nicotine restricted to early gestation also has the potential to affect DNA methylation is unknown.…”
Section: Introductionmentioning
confidence: 99%